2021
DOI: 10.1111/agec.12651
|View full text |Cite
|
Sign up to set email alerts
|

Willingness to pay for a new farm technology given risk preferences: Evidence from an experimental auction in Kenya

Abstract: This paper describes an experimental auction conducted among maize traders and farmers in Western Kenya to measure adoption for two low-cost technologies that can measure grain moisture content. Willingness-to-pay auctions (WTP) were combined with a risk preference lottery, allowing an opportunity to study the impact of risk preferences on technology adoption. The specifics of this technology also allows us to identify the impact of risk aversion on willingness to pay for a technology when production uncertain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…First, we show that households trade-off food quantity and quality in the lean season when overall quality and quantity are both low. In this way our study adds important new information to the existing literature that has demonstrated the benefits of credit, savings and technology interventions that increase income and consumption in the lean season (Aggarwal et al, 2018;Basu & Wong, 2015;Burke et al, 2019;Channa et al, 2021;Chegere et al, 2021;Flory, 2018;Nindi et al, 2021;Omotilewa et al, 2018). However, our results suggest that simply increasing the quantity of food sold and consumed in the lean season may not be sufficient to increase food safety and security.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…First, we show that households trade-off food quantity and quality in the lean season when overall quality and quantity are both low. In this way our study adds important new information to the existing literature that has demonstrated the benefits of credit, savings and technology interventions that increase income and consumption in the lean season (Aggarwal et al, 2018;Basu & Wong, 2015;Burke et al, 2019;Channa et al, 2021;Chegere et al, 2021;Flory, 2018;Nindi et al, 2021;Omotilewa et al, 2018). However, our results suggest that simply increasing the quantity of food sold and consumed in the lean season may not be sufficient to increase food safety and security.…”
Section: Discussionmentioning
confidence: 66%
“…However, many smallholder farmers fail to take advantage of this clear arbitrage opportunity, a phenomenon labeled "sell low and buy high" (Burke et al, 2019). The phenomenon is partially due to storage issues creating physical losses to stored grain (Aggarwal et al, 2018;Kadjo et al, 2016;Omotilewa et al, 2018), cash and liquidity constraints (Basu & Wong, 2015;Burke et al, 2019;Channa et al, 2021;Dillon, 2020;Kadjo et al, 2018;Stephens & Barrett, 2011;Sun et al, 2013), and behavioral and social challenges including commitment issues, impatience, self-control and social pressure to share (Ashraf et al, 2006;Baland et al, 2011;Basu, 2014;Brune et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, while most researchers do not randomize the order in which MPL questions are asked, others have found significant order effects (e.g. Channa et al, 2021). In our application, the order of choices within MPL is an important source of bias in measured WTP, but the order of options within choice has little effect on reported valuations.…”
Section: Introductionmentioning
confidence: 74%
“…Both papers randomize the order within MPL (a small minority among MPL implementations), but also only use the first switch. Fuller and Ricker-Gilbert (2021) do not find an order effect, whereas Channa et al (2021) document a strong order effect among farmers but not traders. It is possible that a full MPL elicitation (i.e., not stopping after the first switch) would have shown order bias in all samples.…”
Section: Application: Wtp For Prepaid Electricity Credit In South Africamentioning
confidence: 95%
“…Thus, overall, farmers face uncertain costs versus benefits when considering whether to adopt straw return technology. As the implementation subject of agricultural technology, farmers' risk preferences are therefore one important factor affecting their adoption of straw return technology (Karlan et al, 2013;Channa et al, 2021). Accordingly, the influence of risk preferences on farmers' adoption of straw return technology mainly occurs in the following ways.…”
Section: Hypothesis Developmentmentioning
confidence: 99%